The Clinicians’ Skills, Capability, and Organisational Research Readiness (SCORR) Tool - Iles-Smith, Heather; Burnett, Carole; Ross, Denise H; Siddle, Heidi J (International Journal of Practice-based Learning in Health and Social Care, 2019)
A research-active healthcare workforce contributes to improved quality of care. Clinicians may be unaware that they are applying early research skills during their everyday practice. Greater understanding of their level of research attainment may improve their awareness and confidence in their research skills. This article describes the development of the Clinicians Skills, Capability, and Organisational Research Readiness (SCORR) Tool, a simple innovation that assesses and captures research skills and attainment at 1) clinician, and 2) organisational level. The SCORR Tool was initially developed to assess levels of research attainment and to promote discussion during annual appraisals for podiatrists working across secondary and community care in a northern region of England. The levels (1 to 5) of attainment recognise UK Health and Care Professions Council (HCPC) registration requirements for chiropodists/podiatrists (Standards 12 to 14). Following testing and feedback, research levels were adapted (Levels 0 to 5) to accommodate all healthcare professionals (with the exception of doctors and dentists). The SCORR Tool may be used individually by clinicians, or in collaboration with their manager, to better understand the level of research attainment and to prompt discussion to increase research activity. It may also be used across a workforce (e.g. during an appraisal) to understand the organisational research readiness. The SCORR Tool requires additional testing and evaluation to validate it as a tool for use across a variety of organisational environments.